Rehabilitation in Parkinson Disease - Dobosiewicz, Anna Maria; Chyba, Piotr; Duda, Grzegorz; Jankiewicz, Małgorzata; Puszcz, Karolina; Zmaczyńska, Teresa (Journal of Education, Health and Sport, 2017)
Parkinson Disease is a neurodegenerative disease which pathogenesis is not well known. Gait and balance disorders are the most basic symptoms of PD. The occurrence of the symptoms depends on phase of disease and patient’s individual attributes. Rehabilitation is one of the possible way to assuage the occurrence of the symptoms. Methods of physiotherapy have to be chosen individually to every patient. Using the methods correctly can help the patient to overcome the symptoms at daily life and improve their quality of life.